Contested Interpretation of Vietnam War Heritage: Tour Guides’ Mediating Roles (Journal of Tourism & Adventure, 2019)
The legacy of the Vietnam War associates Vietnam with being a destination for dark tourism. Located in the central Vietnam, Quang Tri, the former Demilitarized Zone (DMZ) has high density of historical sites left from the Vietnam War. Visitation to the war-related sites for commemoration and secular pilgrimage is among the top motivations for tourists arriving in the city. The current research seeks to investigate the mediating roles of on-site guides at the historical sites of Quang Tri. By observing on-site tour guide performance, analysing their narratives and conducting interviews with guides working at monuments and historical sites, and reflection of tourists visiting the sites, the authors provide a unique perspective of guiding at contested war heritage, where on-site guides perform multiple mediating roles. The findings of the study highlight the need to reappraise the role of on-site guides and have implications for the planning and development of guiding services at historic sites.